Exploring People's Perception on Pros and Cons of Human-Bat Coexistence in Urban Environs in Southwestern Nigeria - Timothy O Ogunbode; Vincent I Esan; Victor O Oyebamiji; Iyabo V Olatubi; Oladotun M Ogunlaran (SAGE Publishing, 2024)
This research intricately explores the dynamics surrounding the coexistence of humans and roosting bats in urban areas, meticulously examining both the advantageous and detrimental aspects of their living arrangement. The study conducted a comprehensive survey with 286 residents in Iwo and Ogbomoso, where Eidolon helvum bats are known to roost, generating a robust dataset for thorough analysis. Rigorous statistical assessments, including the KMO and Bartlett's tests, confirmed the data's reliability at a significance level of P  < .05. The respondent demographic revealed a predominance of 65% male participants, with an overwhelming 85% claiming familiarity with bats in their respective domains. Utilizing factor analysis, the study identified 8 salient variables from the initial 26, shedding light on diverse perceptions regarding bats: (i) Urban roosting (16.729%); (ii) Impact on tree growth (12.607%); (iii) Failed dislodgement attempts (11.504%); (iv) Medicinal value (10.240%); (v) Co-habitation preference (9.963%); (vi) Costly dislodgment consequences (9.963%); (vii) Beautification disruption (5.615%); and (viii) Structure defacement (5.510%). These factors were systematically categorized into 4 distinct themes: (A) Forced cohabitation (26.762%); (B) Environmental degradation by bats (23.732%); (C) Consequences of dislodging bats (21.477%); and (D) Acknowledged benefits of bats (10.240%). Co-habitation with bats becomes a necessity for ecological balance and, importantly, to safeguard the livelihood of roosting bats within their natural ecology, which man has encroached upon through urbanization, making all negatives arising from such existence self-inflicted by man. However, this study underscores the importance of human-bat cohabitation for mutual benefits, emphasizing potential detrimental consequences, including significant costs, associated with displacing bats from their natural ecosystem. These consequences may exacerbate the impacts of climate change, environmental degradation, and ecological imbalance. Further research is recommended to explore the positive aspects of the sustainable roosting bats' existence in the natural environment.